Bezrefleksyjna codzienność refleksyjnych uczniów, czyli polska edukacja wczesnoszkolna z podręcznikiem w tle - Aleksandra Szyller (Problemy Wczesnej Edukacji)
This article presents my own research results. The research consists of the third-graders’ opinions about the textbook role and usefulness in the teaching process and the analysis of children’s experiences connected to the educational packets in the school practice. The qualitative data had been gathered trough focus interviews and enriched with the analysis of students’ works. As the research shows, the children’s negative perception of everyday school life seems to origin in the teachers’ admiration to go through the textbooks page by page and students’ subjection to the textbooks packets. Everyday work with the textbook forces children to make often anti-developmental tasks and to resign from divergent and creative thinking in favor of acting according to the designated algorithm. The modern school with the textbook on the pedestal is changing into a space with growing restrictions. The creation of independent subjects is giving place to the formation of other-directed individuals, lacking of the ability to think reflective, which is an important change catalyst.